THE COLLOCATION METHOD FOR SOLVING NONHOMOGENEOUS FUZZY BOUNDARY VALUE PROBLEMS - Mohammed, Osama H; Fadhel, Fadhel S (Al-Nahrain Journal of Science, 2010)
In this paper, the collocation method is considered to solve the nonhomogeneous fuzzyboundary value problems, in which the fuzziness appeared together in the boundary conditions andin the nonhomogeneous term of the differential equation. The method of solution depends ontransforming the fuzzy problem to equivalent crisp problems using the concept of -level sets